THE IMMERSION EFFECT OF 30% Stenochlaena palustris LEAVES EXTRACT ON DISCOLORATION OF HEAT CURED ACRYLIC RESIN BASE - Danika Dita Maharani; Rahmad Arifin; I Wayan Arya Krishnawan Firdaus (Dentino : Jurnal Kedokteran Gigi, 2022)
Background: South Kalimantan Province is one of the regions in Indonesia with the highest use of dentures with a percentage of 3.3%. Dentures should be cleaned frequently to help maintain their quality, particularly using a denture cleanser. The most widely-used denture cleanser in the community is alkaline peroxide. Alkaline peroxide can effectively inhibit the growth of Candida albicans on dentures. However, long-term use of alkaline peroxide may lead to discoloration of the acrylic resin denture base. The 30% of kelakai leaves extract may be used as an alternative to denture cleanser, because it is recognized to have antifungal properties and is expected to be capable of minimizing the effect of discoloration. Objective: To analyze the immersion effect of 30% kelakai leaves extract on discoloration of heat cured acrylic resin base. Methods: This research was a true experiment with a pretest and posttest design with a control group using a heat cured acrylic resin sample with a diameter of 15mm x 2mm thick. A total of 21 samples were divided into 3 groups of immersion, namely 30% kelakai leaves extract, alkaline peroxide, and aquadest. Samples were measured before and after immersion for 5 days to assess discoloration using a series of digital analysis tools and the CIELAB system. The value obtained is entered in the equation  Results: One Way ANOVA test and Post Hoc Bonferroni statistical test showed that there was a significant difference (p<0.05) between the 30% kelakai leaves extract (7.04 ± 0.31), alkaline peroxide (3.01 ± 0.29), and aquadest (2.31 ± 0.63). Each immersion group indicated significantly different results. Conclusion: There was a change in the color of the heat cured acrylic resin base after immersion in 30% kelakai leaf extract. Keywords: Discoloration, Heat cured acrylic resin, Digital analysis, Stenochlaena palustris leaf, System CIELAB.